Revolución y diplomacia: el Trienio Liberal y América - del Mar Barrientos Márquez, María; Lozano Salado, Lola (Biblioteca de Historia de América, 2023)
This book collects a part of the works developed within the framework of the project research "Andalucia and politics American of the Liberal Triennium (1820-1823)". coordinated by Gonzalo Butrón Prida from the University of Cádiz (Spain) and financed by the Government of Andalucia. The studies gathered here provide new perspectives on approaching the issue Americana on the complex stage opened by the Spanish revolution of 1820. All of them contribute to explaining the failure of the new liberal regime when proposing an exit consensual, both for its resistance to recognize that everything was lost, as for his naive confidence in the ability thaumaturgy of the recovered Constitution Cádiz. Furthermore, as is evident from Throughout the volume, the Liberal Triennium served especially of encouragement and impulse to theindependences.